2002
DOI: 10.1289/ehp.02110307
|View full text |Cite
|
Sign up to set email alerts
|

The association between noise exposure and blood pressure and ischemic heart disease: a meta-analysis.

Abstract: It has been suggested that noise exposure is associated with blood pressure changes and ischemic heart disease risk, but epidemiologic evidence is still limited. Furthermore, most reviews investigating these relations were not carried out in a systematic way, which makes them more prone to bias. We conducted a meta-analysis of 43 epidemiologic studies published between 1970 and 1999 that investigate the relation between noise exposure (both occupational and community) and blood pressure and/or ischemic heart d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
258
1
15

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 395 publications
(281 citation statements)
references
References 46 publications
7
258
1
15
Order By: Relevance
“…Our L eq and L max measures indicate exposure to very loud noise for periods somewhat comparable to the daily ranges associated with increased cardiovascular and psychosomatic health risks. 10,12,15,17,18,20,[33][34][35][36][37] However, we warn that these studies generally treated periodic exposures throughout the day, such as those due to proximity to rail systems or traffic. Most BART trips are likely to extend beyond one line segment; for round-trip commuters, such exposure will double in the course of a day.…”
Section: Discussionmentioning
confidence: 99%
“…Our L eq and L max measures indicate exposure to very loud noise for periods somewhat comparable to the daily ranges associated with increased cardiovascular and psychosomatic health risks. 10,12,15,17,18,20,[33][34][35][36][37] However, we warn that these studies generally treated periodic exposures throughout the day, such as those due to proximity to rail systems or traffic. Most BART trips are likely to extend beyond one line segment; for round-trip commuters, such exposure will double in the course of a day.…”
Section: Discussionmentioning
confidence: 99%
“…9 In contrast to hypertension, fewer studies have looked into the association between RTN and blood pressure (BP), showing close-to-null results and lack of a clear exposure-response relationship in the general population, possibly due to exposure misclassifi cation and effect modifi cation by antihypertensive mediation use. [10][11][12][13][14] Several Bulgarian studies conducted in Sofi a evidenced higher prevalence of hypertension and higher BP in people exposed to day-evening equivalent noise level (L eq 6-22 h ) > 60 dB, but they are dated (2000 -2001) and reported unadjusted results. [15][16][17][18] Also of note, previous studies focused on the general population, rather than on patients with prior diagnosis with CVD, who are arguably more susceptible to the deleterious effect of RTN.…”
Section: Introductionmentioning
confidence: 99%
“…Dzhambov and Dimitrova supported these findings by observing similar findings and reported a positive association between occupational noise and increased BMI [17]. Stress due to general high noise pollution and occupational noise can lead to increase BP, irritation, and sleep disturbance [18]. Similarly, a study from China reported the positive association between occupational noise and hypertension while studying on workers from automobile company [19].…”
Section: Discussionmentioning
confidence: 66%